2022
DOI: 10.3389/fvets.2022.899314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Dairy Goat Diets With Rapeseed Oil or Sunflower Oil on Performance, Milk Composition, Milk Fatty Acid Profile, and in vitro Fermentation Kinetics

Abstract: The aim of this study was to determine the effect of supplementing dairy goat diets with rapeseed oil and sunflower oil on performance, milk composition, milk fatty acid profile, and in vitro fermentation kinetics. Nine Danish Landrace goats with 42 ± 5 days in milk were allocated to three treatment groups for 42 days. Animals received a basal diet, formulated with 85:15 forage:concentrate ratio, and the basal diet was supplemented with either rapeseed oil or sunflower oil at 4% of dry matter. Goat milk was sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This technique allows researchers to have better control over the research environment and eliminate host-related factors that might affect the fermentation process, such as the rumen passage rate and absorption. Different parameters, such as TGP, VFA, CH 4 concentration and yield, dDM, and microbiome composition after fermentation, can be measured in vitro ( Sato et al, 2020 ; Dhakal et al, 2022 , 2023 ; Vargas-Bello-Pérez et al, 2022 ). The dynamics of dDM, TGP, CH 4 concentration, and yield in this study were linear with time up to 36 h, and beyond that, no variation was observed, suggesting that a fermentation with a duration over 36 h is not required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique allows researchers to have better control over the research environment and eliminate host-related factors that might affect the fermentation process, such as the rumen passage rate and absorption. Different parameters, such as TGP, VFA, CH 4 concentration and yield, dDM, and microbiome composition after fermentation, can be measured in vitro ( Sato et al, 2020 ; Dhakal et al, 2022 , 2023 ; Vargas-Bello-Pérez et al, 2022 ). The dynamics of dDM, TGP, CH 4 concentration, and yield in this study were linear with time up to 36 h, and beyond that, no variation was observed, suggesting that a fermentation with a duration over 36 h is not required.…”
Section: Discussionmentioning
confidence: 99%
“…The gas production pressure was measured every 10 min and converted to milliliter of gas produced per gram of incubated substrate. More details on this method can be found in Vargas-Bello-Pérez et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile fatty acid determination was completed as previously reported by Vargas-Bello-Pérez [ 37 ]. To measure volatile fatty acids (VFA), 5 mL of filtered rumen fluid was collected and placed into a 7 mL test tube previously filled with a one mL metaphosphoric solution (5:1 ratio) for VFA determination.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro rumen fermentation can be used to study rumen function, including the degradation of feedstuffs, fermentation kinetics, the production of volatile fatty acids (VFAs), total gas production, the concentration and yield of methane in total gas, the activity of rumen microorganisms, and the effects of feed additives on microorganisms [7][8][9][10]. Fermentation is influenced by the feed type and inoculum source (rumen fluid) and having the same microbial composition before and after the fermentation is desirable.…”
Section: Introductionmentioning
confidence: 99%